Pengaruh Perbedaan Budaya terhadap Interaksi di Himpunan Mahasiswa Program Studi Komunikasi dan Penyiaran Islam UIN Sultan Maulana Hasanuddin Banten - Mochamad Fachru Isyraqi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Cultural diversity within the university environment is an inevitable reality, particularly within student organizations. The Student Association of the Islamic Communication and Broadcasting Study Program (HMPS KPI) at UIN Sultan Maulana Hasanuddin Banten is composed of students from various regions, each bringing distinct cultural backgrounds, languages, values, and communication styles. This study aims to examine the extent to which cultural differences influence social interaction among members of the organization, as well as how they build harmonious communication amidst these differences. The research employs a descriptive qualitative approach, using in-depth interviews, participatory observation, and documentation with active members of HMPS KPI from various academic cohorts. The findings indicate that cultural differences affect communication styles, expression of ideas, decision-making processes, and perceptions of leadership structures. While such differences may sometimes lead to misunderstandings, they also serve as a strength in fostering an inclusive, open, and adaptive organizational atmosphere that welcomes diverse perspectives. In conclusion, cultural differences significantly influence social interactions within student organizations, but these challenges can be effectively managed through inclusive communication and cross-cultural understanding.